Depositional setting, provenance, and tectonic-volcanic setting of Eocene-Recent deep-sea sediments of the oceanic Izu-Bonin forearc, northwest Pacific (IODP Expedition 352) - Robertson, Alastair H. F.; Schindlbeck, Julie Christin (International geology review, 2018)
(2018). Depositional setting, provenance, and tectonic-volcanic setting of Eocene-Recent deep-sea sediments of the oceanic Izu-Bonin forearc, northwest Pacific (IODP Expedition 352) International Geology Review: Vol. 60, No. 15, pp. 1816-1854.